Free and bound states of ions in ionic liquids, conductivity, and underscreening paradox - Feng,G; Kornyshev,A; Goodwin,Z (Physical Review X, 2019)
Free and Bound States of Ions in Ionic Liquids, Conductivity, and Underscreening ParadoxGuang Feng,1, Ming Chen,1 Sheng Bi,1 Zachary A.H. Goodwin,2,3 Eugene B. Postnikov,4 Nikolai Brilliantov,5,6 Michael Urbakh,7, and Alexei A. Kornyshev3,81State Key Laboratory of Coal Combustion, School of Energy and Power Engineering, Huazhong University of Science and Technology, Room 321, Power Building, 1037 Luoyu Road, Wuhan, Hubei 430074 China2Department of Physics, Imperial College London, South Kensington Campus, SW7 2AZ London, United Kingdom3Department of Chemistry, Imperial College London, Molecular Sciences Research Hub, White City Campus, W12 0BZ London, United Kingdom4Theoretical Physics Department, Kursk State University, Radishcheva Str., 33, Kursk 305000, Russia5Department of Mathematics, University of Leicester, University Road, Leicester LE1 7RH, United Kingdom6Skolkovo Institute of Science and Technology, Moscow 121205, Russia7School of Chemistry, The Sackler Faculty of Science, Tel Aviv University, Ramat Aviv, 69978 Tel Aviv, Israel8Thomas Young Centre for Theory and Simulation of Materials, Imperial College London, South Kensington Campus, SW7 2AZ London, United KingdomCorrespondence: gfeng@hust.edu.cn (GF), urbakh@post.tau.ac.il (MU), nb144@leicester.ac.uk (NB) and a.kornyshev@imperial.ac.uk (AAK) ABSTRACTUsing molecular dynamics simulations and theoretical analysis of velocity autocorrelation functions, we study ion transport mechanisms in typical room temperature ionic liquids. We show that ions may reside in two states – free and bound with an inter-state exchange; we investigate quantitatively the exchange process and reveal new qualitative features of this process. To this end we propose a dynamic criterion for free and bound ions, based on the ion trajectory density and demonstrate that this criterion is consistent with a static one, based on interionic distances. Analyzing the trajectories of individual cations and anions, we estimate t